Transformation of the Political System of Saudi Arabia: Regional Dimension - Abdullah Hazaa Othman; Oleg Evgenievich Grishin; M. Yoserizal Saragih; Mulyadi (Budapest International Research and Critics University, 2020)
The Kingdom of Saudi Arabia is considered one of the pivotal countries in the region and the international community due to its political and economic weight. The importance of this role comes with the Saudi weight in the Arab Gulf and the importance of the Gulf for the Kingdom’s security in general, as well as being at the forefront of the countries bordering the Gulf in terms of the volume of output and oil reserves. Since the year 2010, changes in the regional environment of the Kingdom of Saudi Arabia have pushed towards reconsidering some of the problems and challenges to which its policy was exposed, and it has moved towards searching for what it deems best to enhance its security and stability in the region. However, this role is faced with internal, economic, political, social, regional and international challenges, The need to adapt in the formation of its positions on regional issues, in line with the changes that occurred in the structure of the Arab regional system and the decline in the position of some regional actors, which led to the multiplicity of Saudi regional proposals to formulate its strategic directions to confront the state of imbalance in the region, in addition to that. Its keenness to fulfill its obligations towards its regional allies, as is the case in Yemen, Saudi Arabia has benefited from being an effective regional state, but its effectiveness must be negatively affected by what is happening on or around its territory. And that future expectations do not serve this role much.